Pengaruh Komitmen dan Disiplin Kerja Terhadap Kepuasan Nasabah Melalui Kualitas Pelayanan Sebagai Variabel Mediasi pada PT Bank Negara Indonesia KCU Makassar - Jum’ati Jum’ati; Romansyah Sahabuddin; Nurman Nurman; Burhanuddin Burhanuddin; Uhud Darmawan Natsir (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine and analyze the influence of commitment and work discipline on customer satisfaction through service quality as a mediating variable at PT Bank Negara Indonesia KCU Makassar. This study was conducted to determine the extent to which commitment and work discipline can influence customer satisfaction directly and indirectly through service quality. This study uses a quantitative approach with an associative method. Data were collected through distributing questionnaires to 133 respondents who were customers at PT Bank Negara Indonesia KCU Makassar which had previously been determined using the Slovin formula. The data analysis technique used was Partial Least Square (PLS) with the help of the Smart-PLS program to test the direct and indirect relationships between variables. The results of this study indicate that Commitment does not directly influence Customer Satisfaction, but has a significant effect on Service Quality. Work Discipline has a significant effect on Service Quality and customer satisfaction. Service Quality does not have a significant effect on customer satisfaction. In addition, Commitment and Work Discipline do not affect Customer Satisfaction through Service Quality as a mediator. These findings indicate that human resource factors, particularly work discipline, play a more dominant role in increasing customer satisfaction than commitment or service quality directly.